2020
DOI: 10.1371/journal.pone.0236253
|View full text |Cite
|
Sign up to set email alerts
|

Studies of host preferences of wild-caught Phlebotomus orientalis and Ph. papatasi vectors of leishmaniasis in Sudan

Abstract: orientalis (N = 15, 48.4%). Blood meal analysis revealed human DNA in two Ph. orientalis (6.4%), hence, the anthropophilic index was 13.3%. Conclusions Multiplex PCR protocol described here allowed the identification of blood meal sources of many vertebrate species simultaneously. The results indicate that wild-caught Ph. orientalis are anthropophilic in the study areas. Further studies on larger blood-fed sample size are required to validate the potential applications of this technique in designing, monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…The vector nature including species and their preferences for hosts [ 24 ] as well as resting and feeding indoor (endophagic and endophilic) or outdoor (exophagic and exophilic) needed to be accounted for in a more systematic way to better understand the impact of different interventions. The flying pattern of sand flies could also have been investigated more, especially when looking at the association between house structure and leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…The vector nature including species and their preferences for hosts [ 24 ] as well as resting and feeding indoor (endophagic and endophilic) or outdoor (exophagic and exophilic) needed to be accounted for in a more systematic way to better understand the impact of different interventions. The flying pattern of sand flies could also have been investigated more, especially when looking at the association between house structure and leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CL which is caused by L. major in this region, can be found in the central and western states of Sudan, including Northern and Southern Dafur, Northern and Southern Kordofan, Khartoum, and El Gezira ( 74 ). In Sudan, L. major is transmitted by the sandfly species P. papatasi ( 75 , 76 ). A recent study utilizing surveillance data reported that the number of CL cases reported from these states in 2014–2017 increased annually, greatly exceeding the estimates reported by the WHO in 2014 ( 74 ).…”
Section: Sudanmentioning
confidence: 99%
“…Phlebotomine sand flies (Diptera: Psychodidae) are a medically important group of insects widely distributed throughout the world. They are responsible for causing several diseases in humans and other animals, including leishmaniasis, sand fly fever, and human bartonellosis [ 1 3 ]. In southern Thailand, several sand fly-borne pathogens have been detected in various sand fly species, including Leishmania parasites in Sergentomyia ( Neophlebotomus ) gammae , Se.…”
Section: Introductionmentioning
confidence: 99%